(untitled) (Journal of Economics and Sustainability, 2024)
This paper examines the impact of Covid-19 and movement control orders on large manufacturing firms in Penang, a major industrial hub in Malaysia with notable participation in the global value chain and identifies the response strategies undertaken by large manufacturing firms for this crisis. This study employs an exploratory qualitative research analysis based on a purposive sampling technique to gather data using an online semi-structured expert interview, with 22 large local and foreign manufacturing firms in Penang responding to the interview. The findings suggest that most of the firms expected a loss of business revenue, disrupted supply chains, employee redundancy, and an increase in government support. Persevering and innovation strategy is the most popular measure taken on by large manufacturing firms, and none of the firms interviewed choose pure persevering as a sole strategy to combat the crisis. The study provides an understanding of strategic responses undertaken by large manufacturing firms. Besides that, the study provides inputs to the government, industry, and policymakers’ suggested policy interventions to improve future crisis management.